Optimization of pre-transplantation conditions to enhance the efficacy of mesenchymal stem cells - Haque, Nazmul; Abu Kasim, Noor Hayaty; Rahman, Mohammad Tariqur (Ivyspring International Publisher., 2015)
Mesenchymal stem cells (MSCs) are considered a potential tool for cell based regenerative therapy due to their immunomodulatory property, differentiation potentials, trophic activity as well as large donor pool. Poor engraftment and short term survival of transplanted MSCs are recognized as major limitations which were linked to early cellular ageing, loss of chemokine markers during ex vivo expansion, and hyper-immunogenicity to xeno-contaminated MSCs. These problems can be minimized by ex vivo expansion of MSCs in hypoxic culture condition using well defined or xeno-free media i.e., media supplemented with growth factors, human serum or platelet lysate. In addition to ex vivo expansion in hypoxic culture condition using well defined media, this review article describes the potentials of transient adaptation of expanded MSCs in autologous serum supplemented medium prior to transplantation for long term regenerative benefits. Such transient adaptation in autologous serum supplemented medium may help to increase chemokine receptor expression and tissue specific differentiation of ex vivo expanded MSCs, thus would provide long term regenerative benefits.